2002
DOI: 10.1194/jlr.r200011-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial lipase

Abstract: Endothelial lipase (EL) is a newly described member of the triglyceride lipase gene family. It has a considerable molecular homology with lipoprotein lipase (LPL) (44%) and hepatic lipase (HL) (41%). Unlike LPL and HL, this enzyme is synthesized by endothelial cells and functions at the site where it is synthesized. Furthermore, its tissue distribution is different from that of LPL and HL. As a lipase, EL has primarily phospholipase A1 activity. Animals that overexpress EL showed reduced HDL cholesterol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 64 publications
(53 reference statements)
1
21
0
Order By: Relevance
“…In a recent review article, Choi et al (33) commented on an unpublished study showing that mice homologous for EL-null alleles have elevated HDL cholesterol level, an observation that corroborates the data in the current study.…”
Section: El Sequence Variants Are Associated With Plasma Hdl Cholestesupporting
confidence: 75%
“…In a recent review article, Choi et al (33) commented on an unpublished study showing that mice homologous for EL-null alleles have elevated HDL cholesterol level, an observation that corroborates the data in the current study.…”
Section: El Sequence Variants Are Associated With Plasma Hdl Cholestesupporting
confidence: 75%
“…Consequently, EL expression is closely linked with the pathogenesis of atherosclerosis. EL expression is subject to many factors, and can be increased by shear forces that induce inflammation and blood pressure [23], [24]. However, the precise mechanisms that underlie the regulation of EL expression are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Like LPL and HL, the EL protein is secreted and binds to heparan sulfate proteoglycans on the endothelial cell surface, where it interacts with lipoproteins (13)(14)(15). Both overexpression and loss of function studies have shown that EL is important in the regulation of HDL cholesterol levels (16 -19).…”
mentioning
confidence: 99%